The Impact of Contact Sessions and Discussion Forums on the Academic Performance of Open Distance Learning Students - Olivier, Benjamin (International Review of Research in Open and Distributed Learning, 2016)
This study investigated the impact of face-to-face contact sessions and online discussion forums on the academic performance of students at an Open Distance Learning (ODL) university (N = 1,015). t-Tests for independent samples indicated that students who attended a written assignment preparation contact session performed significantly better in the written assignment than those students who did not attend this contact session [t(813) = 4.64, p = 0.00]; students who attended an examination preparation contact session did not perform significantly better in the examination than those students who did not attend this contact session [t(892) = 1.12, p = 0.26]; while students who used an online discussion forum performed significantly better in the final examination than those students who did not use this forum [t(1,013) = 4.04, p = 0.00]. Reasons for these mixed results are subsequently discussed. The study also found that the attendance of contact sessions and the utilisation of an online discussion forum by students were extremely low, and possible reasons for this are also given. Implications for the use of contact sessions and online discussion forums to improve the academic performance of ODL students are also discussed.